Indonesian Language Learning Curriculum for Foreign Speakers (BIPA) based on moderation at UIN Raden Mas Said Surakarta - Elen Inderasari; Dian Uswatun Hasanah; Aminuddin Faryabi; Dede Nugraha Kurniawan (Universitas Ahmad Dahlan, 2024)
This research aims to describe the Moderation-Based BIPA Curriculum of UIN Raden Mas Said Surakarta. This research uses qualitative methods and a phenomenological study approach. Data collection in this research is participant observation, observation, interviews and document analysis. The validity of the data in research uses triangulation of methods and data sources. The data analysis technique used in this research is the Cresswel model of phenomenological data analysis. The research results show that the curriculum management that applies to BIPA learning at UIN Raden Mas Said is 1) planning, which includes curriculum objectives, learning, textbooks, facilities and infrastructure, teaching staff, BIPA teaching methods, evaluation design. 2) organization, including study schedules and student data, tools, learning media and infrastructure, learning and its methods. 3) implementation, including learning activities, lesson plans (RPS) documents, textbooks, teaching methods, BIPA institutions related to teacher attitudes and quality, existence of facilities and infrastructure, evaluation, process and assessment. 4) supervision, which includes graduate competency standards, learning process standards, teacher and tutor standards, and learning assessment standards. Meanwhile, the values ​​of religious moderation found are tawassuth (moderate), tawazun (continuous), i'tidal (straight and firm), tasamuh (tolerant), musawah (equality), shura (deliberation), tathawur wa ibtikar (dynamic and innovative) and tadadhdhur (civilized).